«O que então conscienciosamente escrevi»: Camilo Castelo Branco sobre a crítica de Poesia - Nobre, Ricardo Miguel Guerreiro (2018)
Written and published by Camilo Castelo Branco from 1849 through 1865, the texts included in Esboços de Apreciações Literárias (1865) reflect the author’s evolution of thought and theoretical reflection on the phenomenon that is literature. In spite of an abundant presence of poetical guidelines, it appears to be clear that the theoretic model which encompasses both critical and terminologically Camilo’s criticism is based on doctrines inherited from Classical Antiquity. It is through this connection — mainly to Aristotle — that in this paper I intend to describe and analyse the meta-poetical texts of Esboços de Apreciações Literárias.